Agroindustrial sustainability: Advanced Oxidative Processes (AOP) using brazilian bioabsorbents (Research, Society and Development, 2021)
The objective of this work was to evaluate bioadsorbers from Brazilian agro-industrial residues (banana and cassava peel) to be used in the elimination of the pollutant blue methylene model (MB). In this context, the adsorption process under various experimental conditions (temperature from 25 to 50 ° C, mass of the bio-adsorbents ranging from 0.5 to 1.0 g) was studied, as well as the kinetic modeling using three different models: pseudo-first order, pseudo-second intraparticle order and diffusion. Advanced Oxidative Processes (POA) UVc-AC and UV-C / Shells were subsequently studied under different conditions (temperature from 25 to 50 ° C, and lamp power from 11 to 33 W). The results obtained were promising, where the best results in the adsorption processes were those using the bio-absorbent banana peel, with a mass of 0.5 g and a temperature of 50 ° C. For the POAs used, the best MB degradation kinetics was in the C4 condition (55 ° C, 33 W) using the banana peel residue, showing a satisfactory and efficient agroindustrial residue to be applied in combination with the UV, contributing to the agro-industrial sustainability and for the improvement of water quality parameters.